Нe use of digital educational resources in teaching geometry - Tsukanova V. N. (Digitalization in the education system: best practices and implementation practices, 2024)
modern society is closely connected with the process of informatization. The widespread introduction of computer technologies is gradually taking place. At the same time, one of the priorities of the process of informatization of society is the informatization of education, i.e. the introduction of new information technologies into the education system. The article discusses the main digital educational resources used in teaching geometry, since the role of geometry in the life of society is difficult to overestimate. More than one building project cannot do without fundamental knowledge of geometry, which also helps in the design and creation of innovative medical equipment for computed tomography, magnetic resonance imaging, ultrasound, radiotherapy and surgery.
Keywords: геометрия; geometry; цифровые образовательные ресурсы; задача; problem; динамическая среда GeoGebra; digital educational resources; GeoGebra dynamic environment